Razvoj zavarovanih območij v Sloveniji - Nared, Janez; Perko, Drago (Regionalni razvoj, 2011)
This book ('The development of protected areas in Slovenia') discusses the development of protected areas in Slovenia. Due to Slovenia's natural and cultural diversity, these areas are extensive, and therefore their special features should also be taken into account in efforts to stimulate regional development. Because of the vulnerable relationships that exist within them, protected areas require integrated planning, which should focus not only on protecting biodiversity and natural heritage, but first and foremost on sustainable development and conservation of established relationships between people and the environment, which are reflected in unique cultural landscapes. The authors analyze various aspects of managing protected areas: defining them, legal frameworks, their role in prevention against natural disasters, their special features in terms of management, and so on. Descriptions of individual cases often highlight the importance of including all stakeholders because only in this way is a protected area acknowledged and accepted as a development opportunity and not an obstacle.Volume seeks to identify patterns for development coordination, negotiations, and stimulation that rely on areas' potentials and their conservation, while also making possible their sustainable growth and development.